Taxing work: Some political and economic aspects of labor income taxation - Thomas R. Cusack; Pablo Beramendi (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
This paper examines the development of tax regimes across the OECD countries in the latter part of the 20th century. It pays particular attention to taxes on labor income. A number of results emerge from this examination. First, not only do taxes on labor income represent a major drain on private households; they have become the mainstay of many of these countries' public sector finances. Second, taxes on labor income, and not taxes on capital, appear to be the preferred instrument of finance for those economic and political interests that advocate and support a strong (and thereby expensive) welfare state. There is little “free lunch” to be had in these welfare states; if anything, “socialism in one class” seems to be the rule. Third, while the effort at financing the welfare state this way comes at cost in terms of loss in employment, the magnitude of such loss is inversely related to the degree of wage coordination in the labor market. – – In diesem Beitrag wird die Entwicklung der Steuersysteme in OECD-Ländern über die letzten Jahrzehnte des 20. Jahrhunderts unter besonderer Berücksichtigung der Steuern auf Arbeitseinkommen untersucht. Folgende Resultate können festgehalten werden. Erstens besteht nicht nur der Großteil der Abgabenbelastung für private Haushalte aus Steuern auf Arbeitseinkommen; sie sind vor allem der Grundstock der öffentlichen Finanzen in den betrachteten Ländern. Zweitens scheinen diese Steuern auf Arbeitseinkommen und nicht etwa Kapitalertragssteuern das bevorzugte Finanzierungsinstrument gerade der politischen und ökonomischen Interessenvertreter zu sein, die sich für einen starken und somit teuren Wohlfahrtsstaat aussprechen. Dabei existiert in den Wohlfahrtsstaaten kein sog. ,free lunch', vielmehr scheint der ,Sozialismus in einer Gesellschaftsklasse' an der Tagesordnung zu sein. Drittens lässt sich feststellen, dass diese Art der Finanzierung des Wohlfahrtsstaates Kosten in Form von Arbeitslosigkeit mit sich bringt, deren Höhe sich allerdings invers zum Grad der Koordination auf dem Arbeitsmarkt verhält.
Keywords: H24; J32; J50; J64; 330; Taxation; Partisan Politics; Institutions; Varieties of Capitalism